Histological characteristics of the uterine cavity scraping in women with hyperprolactinemia of various origins, complicated by terminating pregnancy - A.A. Trushkevich; T.G. Filonenko; E.P. Golubinskaya; I.N. Platonova; A.A. Dovgan; A.A. Shirokova (Zaporozhye State Medical University, 2013)
The main morphological feature in spontaneous abortions in hyperprolactinemia of various origin is reduced activity of invasive cytotrophoblast. At the same time a decrease in utero-placental barrier and increased hypoxia, resulting in dystrophic and necrotic processes in decidual tissue and chorionic villi. Delay differentiation of chorionic villi in the form of primary cystic edematous and secondary avascular villi, characteristic mainly for early pregnancy suggests genetically deterministic pathogenesis of hyperprolactinemia. The distinctive morphological feature of scrapings of the uterus in women with missed abortion of miscarriage, is the presence of severe inflammatory reaction and fibrinoid necrosis.